2018
DOI: 10.1002/cplu.201800045
|View full text |Cite
|
Sign up to set email alerts
|

Hexaethylbenzene: A Sterically Crowded Arene and Conformationally Versatile Ligand

Abstract: The syntheses, structures and dynamic behaviour of hexaethylbenzene and its transition metal and main group element complexes are reviewed. Sterically protected intermediates in the metal‐catalysed trimerisation of 3‐hexyne to form hexaethylbenzene are described, and the organic chemistry of hexaethylbenzene and of hexamethylbenzene are compared and contrasted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 143 publications
0
1
0
Order By: Relevance
“…Hexasubstituted arenes have been a topic of interest in organic chemistry due to their high steric strain, which makes them appealing targets for the study of conformational dynamics and aromaticity, as well as their rigidity, which allows for enforcement of unique molecular architectures. The preorganization inherent to the hexasubstituted arene framework has been used in multivalent protein inhibitors, biomimetic dendrimers, molecular “gears” and “propellers”, and many other applications, demonstrating the utility of these unusual synthetic targets.…”
mentioning
confidence: 99%
“…Hexasubstituted arenes have been a topic of interest in organic chemistry due to their high steric strain, which makes them appealing targets for the study of conformational dynamics and aromaticity, as well as their rigidity, which allows for enforcement of unique molecular architectures. The preorganization inherent to the hexasubstituted arene framework has been used in multivalent protein inhibitors, biomimetic dendrimers, molecular “gears” and “propellers”, and many other applications, demonstrating the utility of these unusual synthetic targets.…”
mentioning
confidence: 99%
“…We note parenthetically that hexaethylbenzene (HEB) may be thought of as an "unrestricted" trindane in which the wingtip methylene groups of the cyclopentenyl rings are now untethered, thus leaving them free to rotate. It was shown that the analogous ruthenium complex of HEB, i.e., [(HEB)RuCl 2 ] 2 , also exists as an interconverting doubleand triple-bridged species, but in this case both the double-bridged neutral species, 13a, analogous to 12a, and also the D 3h -symmetric cation, 13b, analogous to 12b, together with its [C 5 (CO 2 Me) 5 ] − counter-anion, have been characterised via X-ray crystallography (Figure 4) [15][16][17]. When [(trindane)RuCl2]2, 12, was allowed to react with excess trindane in the presence of AgBF4, the sandwich compound [(η 6 -trindane)2Ru] 2+ 2[BF4] − , 14, was isolated and fully characterised spectroscopically [14].…”
Section: Trindane Complexes Of Rutheniummentioning
confidence: 99%